1978
DOI: 10.1111/j.1365-2621.1978.tb00771.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low temperature on the growth and survival of Staphylococcus aureus and Salmonella typhimurium when inoculated on to bacon

Abstract: Samples of bacon (10 g) were inoculated with Staphylococcus aureus and Salmonella typhimurium and the effect of storage at -22, 5 and 16°C was studied. The numbers of S. aureus increased significantly at 5 and 16"C, whilst at -22°C a significant decrease was recorded. The S. typhimurium counts increased at 16°C but decreased when the storage temperature was 5 and -22°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was also reported that the survival period of S. aureus was longer at lower temperatures than higher temperatures [22]. In addition, S. aureus inoculated in the bacon could survive at -22°C even after 30 days of storage [23]. Although the mechanism and evidence concerning the higher survival probability of S. aureus at lower temperature are not clarified, some studies indicate that S. aureus increased in glycolytic enzyme production and changed the lipid components of its membrane to acclimate to cold environment [24,25].…”
Section: Resultsmentioning
confidence: 88%
“…It was also reported that the survival period of S. aureus was longer at lower temperatures than higher temperatures [22]. In addition, S. aureus inoculated in the bacon could survive at -22°C even after 30 days of storage [23]. Although the mechanism and evidence concerning the higher survival probability of S. aureus at lower temperature are not clarified, some studies indicate that S. aureus increased in glycolytic enzyme production and changed the lipid components of its membrane to acclimate to cold environment [24,25].…”
Section: Resultsmentioning
confidence: 88%
“…When refrigeration is extended, Pseudomonas, Acinetobacter, and Moraxella species may grow and damage fresh meat [67]. Gram-negative organisms are known to survive less frequently compared to their Gram-positive counterparts [68][69][70]. However, recent studies have shown higher survival rates among Gram-negative bacteria, especially Pseudomonas species, which account for the majority of bacteria responsible for refrigerated meat deterioration [67].…”
Section: Microbiological Propertiesmentioning
confidence: 99%
“…). Studies reported that the limiting water activity (aw) for the growth of S. aureus sealed in canned meat at an oxygen concentration of 5.5% was 0.87% at 37°C and 0.91% at 20°C Farrell GM & Upton ME (1978). seeded S. aureus on strips of bacon and stored them at -22°C, 5°C, and 16°C to monitor the number of bacteria in these strips.…”
mentioning
confidence: 99%